IOR 1997 - 9th European Symposium on Improved Oil Recovery 1997
DOI: 10.3997/2214-4609.201406787
|View full text |Cite
|
Sign up to set email alerts
|

Foams for GOR Control - Improved Stability by Polymer Additives

Abstract: Displacement tests in sandstone cores have been applied to quantify formation of foam and the gas blocking ability of water continuous foams witti polymer additives . The different chemical properties of polymers and their interactions witti surfactants made it intergisting to test botte biopolymers and syrithetic polymers . Love mobility foams veere generated botte in Berea and reservoir corgi material witti AOS baserf foams . The formation of foam witti alphaolefinsulfonate surfactant was little influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 1 publication
(1 reference statement)
2
19
0
Order By: Relevance
“…Some define a critical oil saturation above which foam does not form (see discussion by Schramm, 1994), but several studies show that it is possible to generate strong foams at relatively high oil saturations (Aarra et al, 1997;Mannhardt and Svorstøl, 1999;Mannhardt et al, 2000;Aarra et al, 2002). Another suggests that a high concentration of light hydrocarbons in the oil appears to be the main reason for reduced foam stability (Kuhlman, 1990).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Some define a critical oil saturation above which foam does not form (see discussion by Schramm, 1994), but several studies show that it is possible to generate strong foams at relatively high oil saturations (Aarra et al, 1997;Mannhardt and Svorstøl, 1999;Mannhardt et al, 2000;Aarra et al, 2002). Another suggests that a high concentration of light hydrocarbons in the oil appears to be the main reason for reduced foam stability (Kuhlman, 1990).…”
Section: Introductionmentioning
confidence: 95%
“…Oil in the core during foam experiments has been reported to reduce the propagation velocity of foam through the core (Jensen and Friedmann, 1987;Aarra et al, 1997;Vassenden et al, 1998;Mannhardt and Svorstøl, 1999). Chou (1991) reports that foam propagation without oil depends on the initial condition of the core material.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several published literature suggested that, the strong foam can be generated at relatively high oil saturations (Aarra et al 1997;Svorstøl 1997, 2001). This may be measured by Mobility Reduction factor (MRF).…”
Section: Introductionmentioning
confidence: 99%